Physiological Response of Dairy Goats Based on Differences in Age and Measurement Time - Wijayanti, Dwi; Rismasari, Rismasari (Jurnal Agripet, 2025)
This study aimed to determine the extent to which there were differences in the physiological status of dairy goats of different ages, including body temperature, pulse rate, and respiratory rate, with different measurement times. This study used a 42 factorial completely randomized design (CRD). The data obtained were analyzed using ANOVA and further tested using the Duncan's multiple range test. The results of the study showed that the age of the goats did not have a significant effect on body temperature (P0.05), but had a very significant effect on the pulse and respiratory rate of the goats (P0.01). The measurement time had a very significant effect on body temperature (P0.01) but did not show a significant effect on the pulse and respiratory rate of the goats (P0.05). The correlation between age and measurement time showed a very significant difference in body temperature (P0.01) but no significant difference in pulse and respiration (P0.05). This study concludes that age significantly affect the pulse and breath of goats; measurement time significantly affects body temperature, and there is a very significant correlation between age and measurement time on body temperature of goats.